Maqasid Syariah In The Productive Zakat Program: A Study Of The Economic Impact Of Mustahik - Muhammad Sanusi; Ahmad Djalaluddin; Misbahul Munir; Said Abdelaal Abdelrahman Emam (JURNAL ECONOMINA, 2026)
This research examines the role of productive zakat as an instrument for mustahik economic empowerment through the lens of maqasid sharia using a qualitative approach based on library research. Through descriptive-analytical analysis of classic, contemporary literature and institutional reports on zakat, the research found that a productive zakat program designed holistically based on maqasid sharia produces an empowerment impact that is far more comprehensive and sustainable than conventional consumptive zakat distribution. The literature synthesis identified that the transformation of mustahik into muzakki as the ultimate outcome of the most theologically meaningful zakat empowerment can only be achieved through the integration of business capital, intensive mentoring, program monitoring, and spiritual formation within a coherent program framework based on the five dimensions of maqasid. This research contributes to the development of an operational maqasid-based productive zakat evaluation framework as an alternative to conventional evaluation approaches which are financial-reductionist in nature.